Kajian Fungsi Kepenatuaan dalam 1 Timotius 3:1–7 dan Relevansinya di Gereja Santapan Rohani Indonesia - Ayub Rusmanto; Yohanes Joko Saptono (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
In the Santapan Rohani Indonesia Church, church councils and officials often follow the opinions of prominent figures within independent congregations. This has led to a lack of uniformity in the use of the term “elder.” This study explores the function of eldership based on 1 Timothy 3:1–7, viewing it as a noble task within the church. The researcher uses a qualitative investigative approach to understand perspectives from both the independent congregations and the synod regarding the elder as a noble calling. Data analysis includes verification steps to ensure the accuracy, generalizability, and potential replication of the study. Interview results provide information that is then descriptively broken down into representative constructions. The elder is seen as someone who willingly desires a noble and honorable task—serving the congregation according to God's will. Thus, eldership is understood as a sacred and meaningful calling within the life and ministry of the church.